Efeito residual da adubação fosfatada sobre produção e acúmulo de nutrientes de abóbora - Chaves, Aridênia Peixoto (Universidade Federal Rural do Semi-Árido, 2014)
The use of residual fertilizer through the exploitation of successive crops is possible, mainly with respect to phosphorus, due to its high setting power on the ground. Thus, the aim of this study was to evaluate the residual effect of the production and accumulation of nutrients in pumpkin. The experiment was conducted at the Rafael Fernandes Experimental Farm, in Lagoinha, Mossoro-RN, in the period from February to May 2013. For the characteristics of dry mass and nutrient accumulation we used a randomized block design in a split plot, with the doses of residual phosphorus (0, 45, 90, 135, 180 and 225 kg/ha de P2O5) plots and sampling times (14, 28, 42, 56, 70 and 84 DAT) subplots. And for production traits, we used a randomized block design with doses of residual phosphorus treatments (0, 45, 90, 135, 180 and 225 kg/ha de P2O5). Growth Jacarezinho pumpkin presented sigmoidal behavior with the highest dry matter accumulation in the period from 28 to 70 DAT. The residual dose of 135 kg ha-1 de P2O5 resulted in higher accumulations of NPK, and remaining doses of 180 and 90 kg ha - 1 P2O5 resulted in higher accumulation of Ca and Mg, respectively. The residual dose of 185 kg ha-1 de P2O5 promoted higher productive performance of Jacarezinho pumpkin
Keywords: Cucurbita moschata; Cultivos sucessivos; Fósforo; Marcha de absorção de nutrientes; Produtividade; Cucurbita moschata; Successive crops; Phosphorus; Absorptions of nutrients; Productivity; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA